Validación del método analítico por cromatografía líquida de alta resolución (hplc) para el ensayo de disolución de dexametasona 0,5 mg tabletas” - Ponce Mostacero, Víctor Bernardo (2017)
The validation of methods is an important requirement in the practice of chemical analysis, which guarantees the quality of the drug. In this work we performed the validation of an analytical method by High Performance Liquid Chromatography (HPLC) for the dissolution test of dexamethasone 0.5 mg tablets, specificity, which determines the ability of the method to measure Dexamethasone Acetate, without interference of Parts of the excipients, results in no response of the equipment by the excipient, therefore the method is specific. Linearity; Which measures the ability of the analytical method to produce results that are proportional to the concentration of the analyte, which is demonstrated in the validation when obtaining a correlation coefficient r = 0.9999, with the minimum value being permissible of 0.9900. The accuracy of the analytical method is the degree of agreement or dispersion of the test results. The values of CVf (%) = 2.852%, this value being lower than the specified limit (CVf (%) Less than or equal to 5%), being the precise method. Intermediate precision which expresses variations within a laboratory, in the case of study was variation of analyst and HPLC equipment, for the groups of repeatability of Precision and Intermediate Precision different analyst giving a p-value of 0.063 (> 0.05 ) With the ANOVA statistical test, which shows the groups are statistically the same and for the different HPLC equipment applying the same test for the groups of repeatability of Accuracy and Intermediate Accuracy different equipment giving a p-value of 0.071 (> 0.05) in The statistical test, thus demonstrating that the method is accurate. The Dexamethasone method 0.5 mg tablets for the dissolution test meets the acceptance criteria, established by the Spanish Association of Pharmaceuticals Industry (AEFI).